All Equilibrium solutions of some class of the complex mathematical programming problems - Jasilionis, R. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Ясилионис. Нахождение всех равновесных решений одного класса сложных задач математического программированияR. Jasilionis. Vienos sudėtingų matematinio programavimo uždavinių klasės visų pusiausvyros sprendinių suradimas